Features of the cardiovascular response of young hand-to-hand combat athletes to physical exertion - Vorobyeva, N.V.; Skoblikova, T.V.; Zavalishina, S.Yu.; Dorontsev, A.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to evaluate the functional response of the cardiovascular system of young hand-to-hand combatants with different levels of athletic experience to standardised physical exercise. Methods and structure of the study. The study included 48 young athletes (aged 19.8±0.62 years), systematically engaged in hand-to-hand combat 3-4 times a week. The athletes were divided into three groups by sports experience: 1 year - 19 people, 2 years - 15 people, 3 years - 14 people. The control group consisted of 17 healthy young men (20.1±0.54 years) who had never been involved in sports. Pulse rate, blood pressure, vital capacity of the lungs and endurance indicators were assessed before and after performing a standardized load. Statistical data processing was performed using Student's t-test. Results and conclusions. With increasing sports experience, hand-to-hand fighters showed a decrease in the initial pulse rate and blood pressure, a decrease in the reaction of the cardiovascular system to the load, and an increase in endurance and vital capacity. In the control group, these indicators remained at a lower level and demonstrated less pronounced adaptation to the load. The results confirm the undoubtedly positive effect of regular hand-to-hand combat training in terms of strengthening the cardiovascular system and increasing the overall functional reserves of the body of those involved.